Effect of counselling on health-promoting lifestyle and the quality of life in Iranian middle-aged women: a randomised controlled clinical trial - Karimlou, Vahideh (BMC Health Serv Res, 2019)
BACKGROUND: Promotion of healthy lifestyle is an important strategy. This study was conducted to determine the effects of counselling on health-promoting lifestyle and quality of life in middle-aged women. METHODS: This randomised, controlled, clinical trial was conducted on 102 middle-aged women presenting to health centers in Tabriz, Iran, in 2016–17. Using stratified blocking based on age (40–50 and 50–60 age groups) with block sizes of four and six, eligible middle-aged women were randomly allocated to the intervention and control groups. The intervention group received health-promoting lifestyle counselling over three 45-min sessions. The control group received the routine care provided by health centers. The Health Promoting Lifestyle Profile- II (HPLP-II) and quality of life survey (SF-36) were completed in both group before and four and eight weeks after completion of the intervention. Data were analyzed using the independent t-test and the repeated measures analysis of variance (ANOVA). RESULTS: After adjustment for the baseline values, the repeated measures ANOVA showed that the mean scores of health-promoting lifestyle (adjusted mean difference = 0.91, 95% confidence interval: 0.83 to 0.99, P < 0.001) and quality of life (18.2, 15.75 to 20.66, P < 0.001) were significantly higher in the intervention compared to the control group after the intervention. CONCLUSION: Counselling can improve health-promoting lifestyle and quality of life in middle-aged women. TRIAL REGISTRATION: : IRCT2015122610324N27. Registered 4 February 2016.